2013
DOI: 10.1681/asn.2013060632
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Based Cardiology in Hemodialysis Patients

Abstract: Cardiac events are the major cause of death in hemodialysis patients. Because of the paucity of randomized clinical trials (RCTs) in hemodialysis patients, most cardiovascular therapies in this population are based on observational studies or results extrapolated from studies that excluded hemodialysis patients. However, associations discovered in observational studies do not prove causality, and these studies often report surrogate outcomes rather than clinical end points. Furthermore, interventions that show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 94 publications
0
20
0
3
Order By: Relevance
“…[19][20][21] Studies showed that high-flux membranes are better than low-flux membranes in terms of reducing insulin resistance and cardiovascular mortality and morbidity. [22][23][24] With recent developments in dialysis technology, the inflammation caused by HD is observed less frequently with biologically adaptive membranes; uremic toxins, medium and large molecules are better cleaned; and hyperlipidemia and oxidative stress are observed less frequently.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21] Studies showed that high-flux membranes are better than low-flux membranes in terms of reducing insulin resistance and cardiovascular mortality and morbidity. [22][23][24] With recent developments in dialysis technology, the inflammation caused by HD is observed less frequently with biologically adaptive membranes; uremic toxins, medium and large molecules are better cleaned; and hyperlipidemia and oxidative stress are observed less frequently.…”
Section: Discussionmentioning
confidence: 99%
“…The number of patients on maintenance hemodialysis suffering from end-stage renal disease (ESRD) is approximately 400,000 in the USA [1] and approximately 300,000 in Japan [2]. Cardiovascular disease accounts for 50% of death among these patients [3], with congestive heart failure comprising approximately 25% of death in Japan [2].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with ESRD on maintenance hemodialysis should be considered as different from the general population because they have different cardiovascular disease characteristics and responses to therapy [1,3]. Moreover, periodic hemodialysis therapy jeopardizes their preload to fluctuate non-physiologically.…”
Section: Introductionmentioning
confidence: 99%
“…Because of substantial differences between the clinical profiles of patients with ESRD and those without ESRD [8], the benefit-risk ratios are presumably different in these two groups. However, there have been only a few studies in which relationships between the number of anti-thrombosis (AP and/or anti-coagulant) agents, clinical benefits and adverse events including major hemorrhage were examined [9, 10].…”
Section: Introductionmentioning
confidence: 99%